Obstrüktif uyku apne sendromlu çocuklarda leptin seviyeleri - (:unkn) unknown (My University, 2016)
Obstrüktif uyku apne sendromlu çocuklarda leptin seviyeleriGiriş: Bu çalışmanın amacı çocuklarda leptin seviyeleri üzerinde obstrüktif uyku apne sendromu (OUAS)'nun etkisini değerlendirmektir.Hastalar ve Metod: Habitual horlaması olan çocuklara polisomnografi yapıldı. Uyku çalışmasını takip eden sabah 08.00-09.00 saatleri arasında açlık venöz kan alındı. Apne-hipopne indeksi >= 5/saat olan çocuklar orta-ciddi OUAS, < 5/saat olan çocuklar hafif OUAS/primer horlama grubuna alındı.Bulgular: Çalışmaya 47 çocuk (%51 erkek ve %49 kız; yaş ortalaması 7.8 ± 2.6 yıl) alındı. Yirmi yedi çocuk orta-ciddi OUAS, hafif OUAS/primer horlama grubunda yer aldı. İki grup arasında yaş, cinsiyet ve vücut kitle indeksi açısından anlamlı fark yoktu (p> 0.05). Log serum leptin seviyeleri gruplar arasında farklı değildi (p= 0.749). Çalışma grubunun tümünde log leptin seviyeleri BMI z skoru ile pozitif korelasyon gösterdi (p= 0.001; r= 0.499), fakat log leptin seviyeleri apne-hipopne indeksi, ortalama ve en düşük oksijen satürasyonu ile korelasyon göstermedi.Sonuç: Habitual horlaması olan çocuklarda serum leptin seviyeleri yağ dokusundan etkilenmektedir fakat OUAS şiddetinden etkilenmemektedir.

Introduction: The aim of this study is to assess the effect of obstructive sleep apnea syndrome (OSAS) severity on leptin levels in children. Patients and Methods: Children with habitual snoring underwent overnight polysomnography. Fasting venous blood samples were obtained between 8 AM and 9 AM, following the night of the sleep study. Children with an apnea-hypopnea index of >= 5/h were included in the moderate-to-severe OSAS group while those with an apnea-hypopnea index of < 5/h formed the mild OSAS/primary snoring group.Results: 47 children (51% male and 49% female; mean age 7.8 ± 2.6 years) were recruited. Twenty seven participants were diagnosed with moderate-to-severe OSAS, and twenty children who had AHI < 5 were included in the mild OSAS/primary snoring. The two groups did not differ regarding age, gender and body mass index z score (p> 0.05). Furthermore there were no differences in log serum leptin levels (p= 0.749). Log serum leptin levels correlated with the BMI z score in the whole study group (p= 0.001; r= 0.499) but they were not associated with apnea-hypopnea index, mean and lowest oxygen saturation during sleep.Conclusion: Serum leptin levels are affected by adiposity but not by OSAS severity among children with habitual snoring.
Leptin levels in children with obstructive sleep apnea syndrome
Keywords: Hematoloji; Genel ve Dahili Tıp; Pediatri